Broken English: What to Do with Wongar, the European Migrant Who Became an Aboriginal Writer. Issue 4 (2nd October 2022) - Simic, Zora
Abstract : Streten Božić arrived in Australia in 1960 with a 'European concept' of the country, but his outlook was transformed by the experience of living with Aboriginal communities in the Northern Territory. In the 1970s, he began publishing as B. Wongar and until it was revealed otherwise in 1981, he was assumed to be Indigenous. While his reputation suffered, Wongar remained committed to elucidating the ongoing colonisation of Aboriginal people. This article historicises Wongar's work and its reception in the light of his own self-representation as a Serbian migrant uniquely positioned to sympathise with and comprehend Aboriginal Australia.